Expert System for Diagnosis Skin Disease in Infants With Case-Based Reasoning Method - Nisaa Ratna Marliana; Ahmad Subhan Yazid; Maria Ulfah Siregar (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2013)
Skin is the most vital for children under five years of age (infants) who are susceptible to the disease. The absence of a dermatologist or expert who can diagnose skin disease and offers the solution results in a long process of healing or cause a fatal condition to the patient. Overcoming of it, it is built an expert system that aims to diagnose skin disease in infants and to provide prevention and treatment solutions. This expert system is constructed by using Case-Based Reasoning (CBR), which calculates the similarity to select the cases that are most relevant or appropriate. This study uses the PHP programming language and MySQL as the database server. This expert system makes it easy to diagnose the disease. It can adapt easily and quickly because the knowledge is constructed from cases. As well, It’s able to produce solutions for prevention and treatment based on symptoms experienced by the patient in accordance with the rules.